2017
DOI: 10.1128/iai.00740-16
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Asparagine Catabolism to Salmonella Virulence

Abstract: Salmonellae are pathogenic bacteria that cause significant morbidity and mortality in humans worldwide. Salmonellae establish infection and avoid clearance by the immune system by mechanisms that are not well understood. We previously showed that L-asparaginase II produced by Salmonella enterica serovar Typhimurium (S. Typhimurium) inhibits T cell responses and mediates virulence. In addition, we previously showed that asparagine deprivation such as that mediated by L-asparaginase II of S. Typhimurium causes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…However, a single mutant lacking ansB was partially defective. A complete loss of growth was observed with an ansA ansB double mutant, consistent with previous reports (9). Adding a fraE mutation to either the ansB mutant strain or the ansA ansB mutant strain had no additional effect.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, a single mutant lacking ansB was partially defective. A complete loss of growth was observed with an ansA ansB double mutant, consistent with previous reports (9). Adding a fraE mutation to either the ansB mutant strain or the ansA ansB mutant strain had no additional effect.…”
Section: Resultssupporting
confidence: 91%
“…During our studies of the fra locus of Salmonella, we found that a fraE mutant was only partially defective for growth on F-Asn as the sole carbon source (6). Two other asparaginases (AnsA and AnsB) mediate nitrogen assimilation and contribute to virulence (9)(10)(11). Because AnsA is cytoplasmic and AnsB is periplasmic (12, 13), we postulated that AnsB was contributing to the growth of a fraE mutant on F-Asn.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Salmonella Typhimurium infection induces asparagine deprivation by hydrolyzing asparagine via S . Typhimurium asparaginase, resulting in inhibition of mTOR signaling, Myc expression, T cell activation, and immune responses in the host ( 79 81 ). Using gas chromatography-mass spectrometry based metabolomics, ETEC was found to induce asparagine deprivation in the jejunum of piglets ( 51 ), but not in serum ( 9 ).…”
Section: Aa As Mediators Of Metabolic Cross Talk Between Host and Patmentioning
confidence: 99%
“…A second example of a gastrointestinal bacterial protein that interferes with T cell metabolism comes from Salmonella enterica serovar Typhimurium, which has been reported to directly inhibit primary mouse T cells (55) and is thought to limit availability of asparagine to T cells (56). When assessing a number of cell surface-expressed molecules, no difference was noted in levels of CD69, CD25␣, CD44, and CD62L in cells infected with S. Typhimurium compared to uninfected controls.…”
Section: Proteins That Affect T Cell Activation and Proliferationmentioning
confidence: 99%